Factor Structure of the Vocational Interest Models of Roe and Holland - Lunneborg, Clifford E.; Lunneborg, Patricia W.; Washington Univ., Seattle. Educational Assessment Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
Analyses of interscale relations in 235 college students for the Vocational Preference Inventory and Vocational Interest Inventory, based on interest models of Holland and Roe respectively, suggest that the two-dimensional, circular configuration of occupations of personality types may be an oversimplification which impedes the understanding of the structure of vocational interests. For both interest models four orthogonal dimensions seem necessary to capture interindividual variability: Social vs. Technical, Organizational vs. Outdoor, Science vs. Business, and Artistic. (Author)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Choice; College Students; Correlation; Factor Structure; Interests; Models; Orthogonal Rotation; Statistical Analysis; Vocational Interests; Holland Vocational Preference Inventory -- Vocational Interest Inventory (Mitchell); Reports, Research